Assessment of the Multifactorial Effect on Antimicrobial Sensitivity in Positive Staphylococcus Aureus Clinical Isolates from Assir Region, Saudi Arabia (Journal of Medicine, 2012)
General objectives: This study aimed at assessment of factors affecting antimicrobial sensitivity in Staphylococcus aureus clinical isolates from Assir region, Saudi Arabia. Materials and Methods: In this study, eighty one patients presented with Staph. aureus infections either nosocomial or community acquired infections were involved by collecting nasal swabs from them at Aseer Central Hospital General Lab. These patients were from all age groups and from males and females during the period of Jan 2011- Jun 2011. These samples were undergone variable laboratory procedures mainly; bactech, culture media, antibiotics sensitivity test using diffusion disc test (MIC) and molecular (PCR) for detection of mec A gene. Clinical and laboratory data were recorded in special formats and analyzed by statistical computer program (SPSS). Results: Showed that; Descriptive and analytical statistical analysis were performed and final results were plotted in tables. In Staph aureus MecA gene positive cases (50) showed: Oxacillin/ Mithicillin, Ciprofloxacin and Fusidin resistant in diabetic patients were 13, 26.0%, 9, 18% and 7, 14% respectively and in non diabetic patients were 37, 74.0%, 22, 44% and 20, 40% respectively. While no sensitivity in diabetic and non diabetic patients using Oxacillin/ Mithicillin. In Staph aureus MecA gene negative cases (31) showed: Oxacillin/ Mithicillin, sensitivity in diabetic patients (5, 16.1%) and in non diabetic were (26, 83.9%). While no resistant in diabetic and non diabetic patients. In Ciprofloxacin and Fusidin resistant in diabetic patients were 1, 3.2% and 1, 3.2% respectively and in non diabetic patients were 12, 38.7% and 7, 22.6%respectively. Erythromycin in Staph aureus ( MecA gene) positive cases (50) showed: resistant in age (0-15) years were (5, 10%), (16-50) years were (16, 32%) and ( 50 years) were (12, 24%). Erythromycin in Staph aureus (MecA gene) negative cases (31) showed: resistant in age (0-15) years were (6, 19.3%), (16-50) years were (5, 16.1%) and ( 50 years) were (3, 9.7%). Conclusion: Drugs resistance is a major progressive multifactorial problem facing the treatment of Staph aureus infections. DOI: http://dx.doi.org/10.3329/jom.v13i2.12750 J Medicine 2012; 13 : 152-159